Auditors are watchdogs and not bloodhounds – Duty of auditors to whistleblow revisited - Ida Shafinaz Mohamed Kamil; Sharija Che Shaari; Junaidah Zeno (Penerbit UMS, 2021)
Auditors like to say their role is that of a watchdog (who barks when they see something suspicious) rather than a bloodhound (who searches for something suspicious). Here, the guiding principles of the corporate law for auditors are responsibility and accountability when examining companies’ accounts and submitting the auditors’ reports. There are many incidents where auditors fail to whistleblow the fraud and become part of the companies' wrongful activities, which gravely affect the interests of the shareholders and stakeholders, especially and the public, generally. Such failure to whistleblow may be due to fear for the auditor’s life or simply because the auditor is not under the impression that the duty is not mandatory. Hence, this paper aims to scrutinise the auditors’ duty to whistleblow and determine whether the auditors are effective watchdogs. Employing doctrinal legal research, this paper thoroughly analysed the extent of the auditor’s duty to whistleblow any wrongful activities by examining the relevant legal provisions under the Companies Act 2016, the Capital Markets & Services Act 2007, and the Whistleblower Protection Act 2010, as well as relevant case laws. The paper concludes that although the applicable legal framework has been put in place to empower the auditors to perform their whistleblowing duty, there is still room for improvement in the legal framework so as to allow the auditors to play their role as a watchdog effectively and that the interests of the shareholders and stakeholders are considered and protected.